Willow productivity from small- and large-scale experimental plantations in Poland from 2000 to 2017. (March 2019) - Stolarski, Mariusz J.; Niksa, Dariusz; Krzyżaniak, Michał; Tworkowski, Józef; Szczukowski, Stefan
Abstract: Studies of the production and use of biomass of perennial plants as energy feedstock have been conducted by Polish researchers for over 20 years. One genus of particular interest is Salix spp. L., which occurs naturally in the temperate zone. Experiments concerning the productivity of willow have been conducted mainly on small-scale experimental fields, but there have been studies conducted on large-scale, experimental and commercial plantations. An analysis of the scientific literature found that the mean willow biomass yield was 8.5 Mg ha −1 y −1 d.m. The mean productivity on small-scale experimental fields (11.4 Mg ha −1 y −1 d.m.) was much higher than on large-scale fields (5.7 Mg ha −1 y −1 d.m.), by 4.5, 7.2 and 7.5 Mg ha −1 y −1 d.m. for biennial, triennial and quadrennial harvest cycles, respectively. Meanwhile, when the optimum yield-generating agents were applied (such as cultivar/clone, fertilisation rate or planting density) higher yields were achieved (by 48% and 72%) in small and large-scale experiments, respectively. Considering only the harvest cycle, the highest mean productivity was achieved in the longer cycles, triennial for small-scale experiments and biennial and triennial for large-scale experimental and commercial plantations. Studies conducted using small-scale experiments still play a very important role in the initial phase of studies on the yield-generating factors under analysis and enable their verification in multiple combinations. Meanwhile, farmers and researchers, as well as national policy-making institutions, value data from commercial plantations. However, there have been few papers published so far on the productivity of such plantations in Poland, particularly those describing studies conducted in similar soil conditions in successive harvest cycles. Moreover, studies should be conducted at sites with poor quality soil, i.e. intended for growing energy crops, where the yield is usually smaller than on good soils used in agriculture for the production of food and fodders. Graphical abstract: fx1 Highlights: Studies of the productivity of willow were conducted in Poland for over 20 years. Various clones and cultivars were tested in 1-, 2-, 3-, 4- and 5-year cycles. The mean yield of willow in small-scale experiments was 11.4 ± 6.0 Mg ha −1 y −1 d.m. The highest yield was achieved in 3-year harvest cycles. The mean yield in large-scale experiments was smaller by 50% than in small-scale.